Tipping Points In Transitions Of Socio-Economic Systems (2022)
ABSTRACT: Chapter 4 proposes metrics to study socio-technical systems’ systematic transformation, focusing specifically on tipping points. It is important to note that such points characterise a qualitative change where niches become institutionalised and new rules and practises become dominant.